2020
DOI: 10.3390/cancers12061600
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anillin in Tumour: From a Prognostic Biomarker to a Novel Target

Abstract: Anillin (ANLN), an actin-binding protein, reportedly plays a vital role in cell proliferation and migration, particularly in cytokinesis. Although there have been findings pointing to a contribution of ANLN to the development of cancer, the association of ANLN to cancer remains not fully understood. Here, we gather evidence to determine the applicability of ANLN as a prognostic tool for some types of cancer, and the impact that ANLN has on the hallmarks of cancer. We searched academic repositories including Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 182 publications
(354 reference statements)
1
38
0
Order By: Relevance
“…However, how E2F7 participates in LUAD is still unknown. The ANLN gene encodes an actin-binding protein that contributes to cell growth and migration [ 43 ]. The expression of ANLN is up-regulated in a variety of types of tumors, including lung cancer, and the development of cancers is related to the expression level of ANLN [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, how E2F7 participates in LUAD is still unknown. The ANLN gene encodes an actin-binding protein that contributes to cell growth and migration [ 43 ]. The expression of ANLN is up-regulated in a variety of types of tumors, including lung cancer, and the development of cancers is related to the expression level of ANLN [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting this multifunctional protein may be an effective treatment to prevent breast cancer recurrence 45 . ANLN is an actin binding protein that is reported to play a vital role in cell proliferation and migration, especially in cytokinesis 46 . ANLN is highly expressed in a variety of cancers and promotes the development of cancer 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Anilin actin binding protein (ANLN) which is located on chromosome 7p14.2 and encodes an actinbinding protein containing 1125 amino acids, has been identi ed to play a vital role in actin cytoskeletal dynamics [6][7][8]. Increasing studies have shown that ANLN is highly expressed in multiple cancers, including breast cancer, ovarian cancer, kidney cancer, colorectal cancer, hepatocellular carcinoma, lung cancer, and pancreatic tumors [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%